Dressed six-quark bags at short and intermediate NN ranges; Nuclear Physics A; Vol. 689, iss. 1-2 - Kukulin V. I.; Obukhovsky I. T.; Gutsche T.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Faessler A. (2001, 2001)
Title screen